(untitled) (INTERNATIONAL SEMINAR, 2024)
Personal branding development is an important aspect of competing in the Industrial Revolution 4.0 era, which is characterized by technological advances and increasingly competitive market demands. This study aims to identify four core skills-communication, adaptability, professional networking, and selfpromotion-as the foundation of effective personal branding. Using a descriptive quantitative approach, with a 20-item questionnaire as the instrument, the study involved a survey of 21 young professionals in the technology and creative sectors. Results showed a significant relationship between the mastery of these core skills and the enhancement of an individual’s personal branding. The findings highlight the importance of technological adaptation, communication skill development, utilization of professional networks, as well as appropriate self-promotion strategies in building reputation and career sustainability. This research provides practical and theoretical contributions for individuals who want to build strong personal branding in the digital age.